Auswirkungen der zunehmenden Wasserverknappung auf die globale und regionale Nahrungsmittelproduktion - Ringler, Claudia; Rosegrant, Mark W.; Cai, Ximing; Cline, Sarah A. (Analytica Verlag, 2005)
For many people, particularly in developing countries, water scarcity will become a part of their livelihoods. The business-as-usual (BAU) scenario shows that in the year 2025, food insecurity and water scarcity will increase. If demand from industry and domestic sectors grows further, and if no more resources are made available for irrigated agriculture, agriculture, poorer economies, and particularly the poorest population in these economies, will be confronted with lower food production and reduced access to agricultural markets. In principle, supply constraints could be substituted by food imports, but only if adequate financial resources are made available. Since this is not likely, water policy changes and institutional reforms are needed such as the implementation of economic incentives to enhance the productivity of water.